Hemorrhagic and clotting abnormalities in infectious bursal disease in specific-pathogen-free chicks - Shiferaw, Tesfaheywet Zeryehun; Bejo, Mohd Hair; Abdullah, Rasedee (IDOSI Publications, 2012)
Investigation to know the hemorrhagic and clotting mechanisms in very virulent (vv) infectious bursal disease virus (IBDV) infection of Malaysian isolate was carried out in chicks. One-hundred-ten, 32-dayold Specific-pathogen-free chicks were divided into IBD and control groups, each consisting 55 chicks. The IBD group was inoculated orally with 0.1 mL/chick of inoculums containing vvIBDV isolate with a titre of 10 EID /mL, while the other group served as controls. Four chicks each in IBD and control groups were 6.8 50 sacrificed at 1, 3, 6 and 12 hours and days 1, 2, 3 and 4 post-infection (pi). Blood sample were collected for thrombocyte count and coagulation tests prior to necropsy. On necropsy gross lesions were recorded. The IBDV infected chicks showed clinical signs of acute disease starting day 2 pi. At days 3 and 4 pi significant (p<0.05) thrombocytopenia and prolonged activated partial thromboplastin time (APTT), prothrombin time (PT) and whole blood recalcification time (WBRT) were recorded corresponding to the occurrence of higher frequency of hemorrhage in the bursa of Fabricus, thigh muscle and mucosal junction between proventriculus and gizzard, which indicate the presence of clotting deficiency. Hence, it was concluded that the vvIBDV of Malaysia isolates caused clotting abnormality that are consistent with the pathogenesis of the disease and it appears that this abnormality in vvIBDV infection could be due to thrombocytopenia and/or coagulation factors deficiencies, or both.